2017
DOI: 10.1186/s12889-017-4110-5
|View full text |Cite
|
Sign up to set email alerts
|

Building social capital to promote adolescent wellbeing: a qualitative study with teens in a Latino agricultural community

Abstract: BackgroundLatino youth, particularly in rural settings, experience significant disparities in rates of teen pregnancy and violence. Few data are available regarding social and structural influences on Latino youth’s developmental trajectories, specifically on factors that promote wellbeing and protect them from engagement in high-risk sexual and violence-related behaviors.MethodsForty-two youth aged 13 to 19 years old were recruited from middle schools and youth leadership programs to participate in one of eig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
22
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 35 publications
(34 reference statements)
9
22
0
1
Order By: Relevance
“…With medical model transformation from a biomedical model to a bio-psycho-social model, recent evidence has been show that factors such as social capital [5], social integration [6] and social-economic factors (gender, education, marital status, immigrant status) may be important for migrant older adults' health. Among them, social capital and social integration were popular in international health research [7] and social science disciplines as well as the field of public health [8,9]. Nan Lin [10] and other researchers [11,12] defined social capital from different perspectives.…”
Section: Introductionmentioning
confidence: 99%
“…With medical model transformation from a biomedical model to a bio-psycho-social model, recent evidence has been show that factors such as social capital [5], social integration [6] and social-economic factors (gender, education, marital status, immigrant status) may be important for migrant older adults' health. Among them, social capital and social integration were popular in international health research [7] and social science disciplines as well as the field of public health [8,9]. Nan Lin [10] and other researchers [11,12] defined social capital from different perspectives.…”
Section: Introductionmentioning
confidence: 99%
“…They argue that expanding the horizons of low-income, minority youth to include others from different areas and backgrounds fosters positive attitudes toward alternative paths to adulthood and deferring early parenting. In a similar vein, a recent qualitative study found that Latino youths described families and immediate surroundings rich with bonding social capital, but despite these youth’s strong social ties, they often lacked the bridging social capital that would help youth navigate complex structures and systems (e.g., educational settings and college applications) that would, in the long-term promote delayed childbearing/fathering and overall upward social mobility [ 71 ]. Ultimately, our study’s findings suggest that future inquiry should attempt to measure each domain of social capital and consider neighborhood scale and respondents’ operationalization of such in order to further sort out the complexity of this finding.…”
Section: Discussionmentioning
confidence: 99%
“…Further, SCT asserts that individuals' self-efficacy beliefs are influenced by the vicarious experience of socialization agents and that self-efficacy further contributes to an individual's motivation to take action [15]. Given the key role of social relationships and socialization agents according to SCT, it is not surprising that adolescents with positive social relationships with parents, peers, and teachers benefit from these experiences and, therefore, are more likely to display better social, emotional and behavioral outcomes [17][18][19][20][21]. In the present study, we investigate if and how social relationships with key socialization agents (measured as relationships with parents, bullying victimization via peers, and relationships with teachers) are directly associated with adolescents' willingness to intervene in bullying, as well as indirectly through self-efficacy in social conflicts.…”
Section: Introductionmentioning
confidence: 99%